LDPC Coding Scheme for Improving the Reliability of Multi-Level-Cell NAND Flash Memory in Radiation Environments - Ge, Guangjun; Yin, Liuguo (China communications, 2017)
Utilizing commercial off-the-shelf（COTS） components in satellites has received much attention due to the low cost. However, commercial memories suffer severe reliability problems in radiation environments. This paper studies the low-density parity-check（LDPC） coding scheme for improving the reliability of multi-level-cell（MLC） NAND Flash memory in radiation environments. Firstly, based on existing physical experiment works, we introduce a new error model for heavyion irradiations; secondly, we explore the optimization of writing voltage allocation to maximize the capacity of the storage channel; thirdly, we design the degree distribution of LDPC codes that is specially suitable for the proposed model; finally, we propose a joint detection-decoding scheme based on LDPC codes, which estimates the storage channel state and executes an adaptive log-likelihood ratio（LLR） calculation to achieve better performance. Simulation results show that, compared with the conventional LDPC coding scheme, the proposed scheme may almost double the lifetime of the MLC NAND Flash memory in radiation environments.